If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5a + -6 = 2a + 6 Reorder the terms: -6 + 5a = 2a + 6 Reorder the terms: -6 + 5a = 6 + 2a Solving -6 + 5a = 6 + 2a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-2a' to each side of the equation. -6 + 5a + -2a = 6 + 2a + -2a Combine like terms: 5a + -2a = 3a -6 + 3a = 6 + 2a + -2a Combine like terms: 2a + -2a = 0 -6 + 3a = 6 + 0 -6 + 3a = 6 Add '6' to each side of the equation. -6 + 6 + 3a = 6 + 6 Combine like terms: -6 + 6 = 0 0 + 3a = 6 + 6 3a = 6 + 6 Combine like terms: 6 + 6 = 12 3a = 12 Divide each side by '3'. a = 4 Simplifying a = 4
| 2+a=a+b+c+d | | 12hk-h^2-20k^2=0 | | 3(2)+2= | | p^2-32q^2-14pq=0 | | 15m^2+2mn-8n^2=0 | | -p^2+3q^2-2pq=0 | | 0=a+b+c+d+e | | x^2+13xy+40y^2=0 | | 8a^2-10ab-3b^2=0 | | 6p^2-19pq+10q^2=0 | | 3c^2-11cd-4d^2=0 | | p^2+5pq-36q^2=0 | | m^2+10mn+21n^2=0 | | 17x^2-12x-5x^3=0 | | 2y+6z-5y-4z= | | 100y+25=50 | | 3y^2*5y= | | 2g+2=5g+14 | | 9x-13=5x+10 | | 12-9x=92-37x | | 8w-10+2w=14+11w+4 | | 22x-4xy-7x-3xy= | | y=x^2-7x+3 | | 3x+4=64 | | 3x-xy-3x+xy= | | 7a+49=-249 | | 3(x+1)=-2-2(x-3) | | 127-3x=2x+10 | | 21-2n=3n-14 | | 5x-16=18x+23 | | 5x-16=18x-23 | | 6X-5X-4=0 |